(untitled) (Universal International Scientific Journal, 2026)
This article discusses the issues of ensuring mental health in the process of training highly qualified personnel in the conditions of globalization. The importance of using innovative pedagogical and psychological approaches in the modern education system is analyzed. The study also highlights methods and technologies aimed at strengthening psychological stability, increasing stress resistance, and developing students’ emotions.